O estudo da perspectiva cavaleira: uma experiência no ensino médio - Kodama, Yumi (2006)
This paper has for objective to investigate the appropriation of the rules of the perspective cavaliere, for pupils of High School, from the shadows of objects and of a computer-based environment and if such rules favor the resolution of problems of Space Geometry. The research was based on the inquiries of Bernard Parzysz (1989, 1991, 2001) on plain representations of space figures, on the works of Paolo Boero (1996) on the production of conjectures of the pupils from the experience with solar shadows and on the works of Chaachoua (1998) on the modifications produced for a computer-based environment in the relations of the subjects on mathematical objects. We use as research methodology, a sequence of activities based on some principles of the didactic engineering that was applied to a group of 7 pupils of grade of High School. The productions of the pupils showed that a dialectic play between concrete geometry and space-graphic geometry contributes for the appropriation of the rules of the perspective cavaliere. However, the analysis of this sequence of education pointed that the perspective cavaliere was used only as one technique of drawing and not as a tool to assist in the resolution of problems of Space Geometry. Other sequences of education could be conceived to study the complexity of that passage